The impact of risk-taking on firm innovation and performance: based on Chinese manufacturing enterprises - WEI, QIANAO (2022)
This article's goal was to serve as a guidepost for Chinese manufacturers by investigating the impact of increased innovation investment on corporate performance and if the effect of technology innovation investment on enterprise performance varies with the degree of risk exposure.As for the method of Dissertation，the literature on risk-taking, innovation, and firm success is described, and then two foundational economic theories—stakeholder theory and the theory of technical innovation—are given for further examination. In the empirical analysis section，we conducted a pairwise analysis of these three variables and offer three hypotheses to help us build useful models. The last step is to use Stata15.0 to run descriptive statistics, correlation analysis, and multiple linear regression on the data to see whether the hypotheses hold up.Meanwhile，in the subsequent empirical analysis, this paper conducted group regression on the basis of the overall regression of the industry, and split the firms in the chosen industry into big enterprises,small and medium-sized enterprises in order to increase the persuasive value of the empirical data.The regression results shown that most manufacturing enterprises can verify the hypothesis.However, that there is a degree of heterogeneity in the effect that size and sector have on the outcomes. When compared to other sectors, the medical manufacturing business is one where risk has a negligible effect on innovative performance. Investing in innovation has a more noticeable effect on the success of large-scale businesses than it does on small and medium-sized ones.